ÐŸÑ€Ð¾Ð½Ð¸Ñ†Ð°ÐµÐ¼Ð¾ÑÑ‚ÑŒ Ð¼ÐµÐ¼Ð±Ñ€Ð°Ð½ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² ÐºÑ€Ñ‹ÑÑ‹ Ð¸ ÐºÑ€Ð¾Ð»Ð¸ÐºÐ° Ð´Ð»Ñ ÐºÑ€Ð¸Ð¾Ð¿Ñ€Ð¾Ñ‚ÐµÐºÑ‚Ð¾Ñ€Ð¾Ð² Ñ€ÑÐ´Ð° Ð°Ð¼Ð¸Ð´Ð¾Ð² Ð¸ Ð´Ð¸Ð¾Ð»Ð¾Ð² - Kovalenko, G. V.; Kovalenko, I. F.; Linnik, T. P. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
As a result of the performed experiments the permeability of rat and rabbit erythrocyte membranes for substances was revealed as dependent on a chemical structure, geometric parameters of molecules, physical and chemical properties of these compounds, in particular hydrophilic and hydrophobic balance of their molecules. The permeability of substances through rat erythrocyte membrane was established as higher than the rabbit one, that was stipulated by the species-specificity of these cells.